Further Education and Training in Ireland: Past, Present and Future - Mc Coy, Selina; Smyth, Emer; Banks, Joanne (ESRI, 2014)
The establishment of An Seirbhís Oideachais Leanúnaigh agus Scileanna (SOLAS) has prompted an assessment of the nature of current further education and training (FET) and an exploration of future directions. This report provides an evidence base for the purposes of assisting SOLAS in the development of a five-year action plan for the Irish FET sector and an associated strategy implementation plan. This research attempts to map provision across the FET sector in order to identify the main issues facing the FET sector. The full extent of FET provision in the State is very broad ranging and includes many actors in addition to the major providers, the former VECs and FÁS. 2 The research draws on (a) a desk-based study drawing together available data from a wide range of sources (b) evidence from semi-structured interviews with key stakeholders and (c) a series of reports commissioned from a number of international experts describing FET provision in their home countries under a number of specified themes. The evidence collected is designed to inform both the SOLAS strategic plan and associated implementation plan.
PUBLISHED
Dublin
Keywords: Education; Inclusive Society; EDUCATION